PENGEMBANGAN MODEL MANAJEMEN PEMBELAJARAN DIRECT INTRUCTION BERFOKUS FILM DALAM PENGANTAR PRAKTIKUM IPA - Saputro, Budiono (Holistik: Journal for Islamic Social Sciences, 2016)
The response introductory practicum Natural Sciences have  not  been maximum results, so that the necessary development of learning management model of direct instruction. This research approach Research & Development (R & D). Subjects were students in. This research was initiated preliminary studies, training needs analysis, FGD, model development, model of learning management guidelines focused direct instruction films and test models of direct instruction teaching learning management. Individual testing, the test group and the limited trial is an attempt to determine the effectiveness of the learning management model focused direct instruction films developed. Data analysis by descriptive and analytical (test wilxocon). Results of a survey of learning management offer direct instruction in primary education: (1) lecturers have not been using the medium of film to convey practical introduction to the theory, (2) pre-tests and post-tests are rarely performed. This research resulted in the learning management model focused direct instruction films and guidelines easier to understand and run. Management stages, namely: planning, implementation, and evaluation. This is evident in a limited test results that there is an increase between pretest to posttest results of students in primary (wilxocon test = 0.00, p <0.05). The conclusions of this research is direct instruction model of learning management focused films can effectively improve the ability of students in a science practicum. Keywords: Direct Instruction; Management: Science PracticumResponsi pengantar praktikum Ilmu Pengetahuan Alam (IPA) belum memberikan hasil yang maksimal, sehingga diperlukan pengembangan model manajemen pembelajaran direct instruction. Penelitian ini menggunakan pendekatan Research & Development (R&D). Subyek penelitian adalah mahasiswa PGMI. Penelitian ini diawali studi pendahuluan, analisis kebutuhan pelatihan, FGD, pengembangan model, panduan model manajemen  pembelajaran direct instruction berfokus film dan uji model manajemen pembelajaran pembelajaran direct instruction. Uji coba perorangan, uji coba kelompok dan uji coba terbatas merupakan upaya untuk mengetahui efektifitas model manajemen  pembelajaran direct instruction berfokus film dikembangkan. Analisis data secara diskriptif dan analitik (uji wilxocon). Hasil survey terhadap manajemen pembelajaran direct instruction di Jurusan PGMI: (1) dosen belum menggunakan media film dalam menyampaikan pengantar teori praktikum, (2) pre-tes dan pos-tes jarang dilakukan. Penelitian ini menghasilkan model manajemen pembelajaran direct instruction berfokus film dan panduan yang lebih mudah untuk dipahami dan dijalankan. Tahapan manajemennya, yaitu: perencanaan, pelaksanaan, dan evaluasi. Hal tersebut terbukti pada hasil uji terbatas bahwa terdapat peningkatan antara hasil pretes dengan postes mahasiswa PGMI (uji wilxocon = 0.00, p < 0.05). Simpulan penelitian adalah  model manajemen pembelajaran direct instruction berfokus film efektif dapat meningkatkan kemampuan mahasiswa dalam praktikum IPA. Kata kunci: direct instruction; manajemen; praktikum IPA